Shaping the future of Cassava production in Southeast Asia: Challenges, trends, and strategic priorities to 2050 - Schiek, Benjamin; Andrade, Robert; Delaquis, Erik; Newby, Jonathan; Cuellar, Wilmer; Petsakos, Athanasios; Gotor, Elisabetta (2025)
This brief provides a comprehensive overview of cassava production and yield trends across key countries in Southeast Asia. Drawing on expert insights gathered in 2024, it examines agronomic, environmental, and policy factors affecting future yield projections. It identifies emerging challenges and opportunities in the cassava sector to inform evidence-based policymaking, guide strategic investments, and support stakeholders in enhancing regional industrial agriculture and sustainable growth.